Binge Drinking and Eating Problems in Russian Adolescents. (20th February 2015) - Stickley, Andrew; Koyanagi, Ai; Koposov, Roman; McKee, Martin; Murphy, Adrianna; Ruchkin, Vladislav
<x xml:space="preserve">Abstract</x> Background Binge drinking may be linked to problematic eating behavior, although as yet, little research has been conducted on this association. The objective of this study was to examine the relationship between binge drinking and eating problems in Russian adolescents. Methods Data were drawn from the Social and Health Assessment, a cross‐sectional school‐based survey of 6th to 10th grade students (aged 12 to 17 years old) carried out in Arkhangelsk, Russia. Information was collected on various eating problems (worries about weight, feeling fat, excessive eating, fasting and excessive exercise, and purging behaviors) and binge drinking (5 or more drinks in a row). Logistic regression analysis was used to examine the relationship between binge drinking and eating problems. Results Among the 2, 488 adolescents included in the statistical analysis, nearly 50% of girls expressed worries about their weight, while 35.0 and 41.5% of adolescent boys and girls reported excessive eating, respectively. The prevalence of purging behaviors (vomiting/using laxatives) was, however, much lower among both sexes (females—2.6%; males—3.3%). In a regression model adjusted for demographic factors and depressive symptoms, among girls, binge drinking was associated with 5 of the 6 eating problems with odds ratios (ORs) ranging from 1.21 (upset about weight gain) to 1.68 (excessive eating). For boys, binge drinking was linked to feeling overweight (OR: 1.47, confidence interval [CI]: 1.20 to 1.81) and vomiting/used laxatives (OR: 4.13, CI: 1.58 to 10.80). Conclusions Many adolescents in Russia report problematic eating attitudes and behaviors, and eating problems are associated with binge drinking. More research is now needed in this setting to better understand adolescent eating problems and their association with alcohol misuse, so that contextually suitable interventions can be implemented to reduce these behaviors and mitigate their potentially detrimental effects.